Miniscrew-assisted rapid palatal expansion for managing arch perimeter in an adult patient - Cunha,Amanda Carneiro da (2017)
ABSTRACT Introduction: Etiology of dental crowding may be related to arch constriction in diverse dimensions, and an appropriate manipulation of arch perimeter by intervening in basal bone discrepancies cases, may be a key for crowding relief, especially when incisors movement is limited due to underlying pathology, periodontal issues or restrictions related to soft tissue profile. Objectives: This case report illustrates a 24-year old woman, with maxillary transverse deficiency, upper and lower arches crowding, Class II, division 1, subdivision right relationship, previous upper incisors traumatic episode and straight profile. A non-surgical and non-extraction treatment approach was feasible due to the miniscrew-assisted rapid palatal expansion technique (MARPE). Methods: The MARPE appliance consisted of a conventional Hyrax expander supported by four orthodontic miniscrews. A slow expansion protocol was adopted, with an overall of 40 days of activation and a 3-month retention period. Intrusive traction miniscrew-anchored mechanics were used for correcting the Class II subdivision relationship, managing lower arch perimeter and midline deviation before including the upper central incisors. Results: Post-treatment records show an intermolar width increase of 5 mm, bilateral Class I molar and canine relationships, upper and lower crowding resolution, coincident dental midlines and proper intercuspation. Conclusions: The MARPE is an effective treatment approach for managing arch-perimeter deficiencies related to maxillary transverse discrepancies in adult patients.